CHARACTERIZATION OF ENVIRONMENTAL INEQUALITIES AMONG A MINING TOWN'S NEIGHBORHOODS CASE STUDY: OUENZA – EAST OF ALGERIA - Berrahail Guendouze,; Soufiane Sid Ahmed,; Brahim Djebnoune, (International Journal of Innovative Technologies in Social Science, 2024)
The waste resulting from mining can contaminate waterways or seep into soils and seriously pollute the environment; therefore it can impact the health of residents. However, these impacts are often deemed differently by this population. This difference is commonly called: "Environmental inequalities". This article spots the light on characterizing environmental inequalities in the mining town: Ouenza, which is located in the extreme east of Algeria. Through a questionnaire conducted in five areas of the town and using sphinx software to analyze results by CFA, we attempted to identify the impact of the extraction activity in this town and to determine the inequalities among the different zones and the factors behind them such as the proximity or the direction of wind.